MOVPE growth and characterization of quaternary Ga(PAsBi)/GaAs alloys for optoelectronic applications. (December 2016) - Nattermann, L.; Ludewig, P.; Knaub, N.; Rosemann, N.W.; Hepp, T.; Sterzer, E.; Jin, S.R.; Hild, K.; Chatterjee, S.; Sweeney, S.J.; Stolz, W.; Volz, K.
Graphical abstract: Highlights: Calculation of band gap and spin-orbit split-off energies of Ga(PAsBi) for different compositions. Temperature-dependent PL and comparison with theory. High-quality MOVPE growth of Ga(PAsBi). Surface and interface investigations on Ga(PAsBi) on an atomic scale. Comprehensive growth studies on Ga(PAs) and Ga(PAsBi) materials. Abstract: Dilute bismide Ga(PAsBi)-based structures are promising candidates for highly efficient optoelectronic applications, like the 1 eV sub-cell in multi-junction solar cells or the active region in infra-red laser diodes. The band gap can be tuned independently from the lattice constant, which theoretically enables the deposition of lattice-matched layers in a wide range of band gap energies on GaAs substrate. In this work, firstly, the shifts in the band edge positions as a function of composition that are possible with the Ga(PAs(Bi)) alloy were estimated using the virtual crystal approximation and valence band anti-crossing theory. Secondly, systematic investigations on MOVPE growth of Ga(PAsBi) layers are presented. Finally, we show the first photoluminescence activity of quaternary Ga(PAsBi) and compare the experimental results to theory.